2020
DOI: 10.1101/2020.08.18.255877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug Repurposing Screen for Compounds Inhibiting the Cytopathic Effect of SARS-CoV-2

Abstract: Drug repurposing is a rapid approach to identifying therapeutics for the treatment of emerging infectious diseases such as COVID-19. To address the urgent need for treatment options, we carried out a quantitative high-throughput screen using a SARS-CoV-2 cytopathic assay with a compound collection of 8,810 approved and investigational drugs, mechanism-based bioactive compounds, and natural products. Three hundred and nineteen compounds with anti-SARS-CoV-2 activities were identified and confirmed, including 91… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…However, the IC 50 of Aloxistatin (21.78 µM) was similar to that of BHH (21.72 µM) ( Table 1 and 2). The IC 50 values that we observed for the reference compounds are consistent with earlier reports [44][45][46][47] . While writing this manuscript, we found that other cellular studies tested BHH and AMB at certain or single concentrations [48][49][50] ; however, this is the first study to our knowledge to conduct the IC 50 evaluation for BHH and AMB against the novel SARS-CoV-2 infection induced CPE.…”
Section: Sars-cov-2 Infection Induced Cytopathic Effect (Cpe) In Verosupporting
confidence: 92%
“…However, the IC 50 of Aloxistatin (21.78 µM) was similar to that of BHH (21.72 µM) ( Table 1 and 2). The IC 50 values that we observed for the reference compounds are consistent with earlier reports [44][45][46][47] . While writing this manuscript, we found that other cellular studies tested BHH and AMB at certain or single concentrations [48][49][50] ; however, this is the first study to our knowledge to conduct the IC 50 evaluation for BHH and AMB against the novel SARS-CoV-2 infection induced CPE.…”
Section: Sars-cov-2 Infection Induced Cytopathic Effect (Cpe) In Verosupporting
confidence: 92%
“…Thus, redefining antiviral strategies should be contemplated beyond expeditious drug repurposing efforts. So far, collective large and multidisciplinary datasets from viral transcriptome (Kim et al, 2020a), host transcriptional response (Blanco-Melo et al, 2020), ribosome profiling (Finkel et al, 2020), whole proteomics (Bojkova et al, 2020), protein-protein interactions by co-IP (Gordon et al, 2020) and proximity labeling (St-Germain et al, 2020), phosphoproteomics (Bouhaddou et al, 2020), RNA structure (Lan et al, 2020), genome-wide CRISPR screen (Wei et al, 2020), and off-label drug screening (Chen et al, 2020) have all provided invaluable insights of the underlying biology of this novel human coronavirus.…”
Section: Resultsmentioning
confidence: 99%
“…It currently consists of six ML models that represent six assays using data from the NCATS (National Center for Advancing Translational Sciences) COVID19 portal ( 43 ). These assays are: the SARS-CoV-2 cytopathic effect, CPE (LVI) ( 44 ); Vero E6 host cell cytotoxicity (LVI counterscreen); Spike-ACE2 protein-protein interaction (AlphaLISA; VE) ( 45 ), TruHit (VE) counterscreen; angiotensin-converting enzyme 2 (ACE2; VE) inhibition; and 3C-like proteinase (3CL or Mpro; VR) inhibition ( 46 ). These models use chemical structures (or drug names; or PubChem CIDs) as input; a similarity search retrieves similar compounds in the NCATS dataset, and sorts them according to the Tanimoto similarity score.…”
Section: New Data and Functionalitymentioning
confidence: 99%